Functional and radiological outcome of surgical fixation of distal femur fractures by distal femoral locking plate in a tertiary care hospital in North India - Singh, Simranpreet; Arif, Mudasser; Gupta, Anil (International Journal of Research in Medical Sciences, 2021)
Background: the aim of the study was to the functional and radiological outcome of fracture of distal femur treated by open reduction and internal fixation with locking compression plate. Methods: A prospective cohort study was conducted on patients admitted in orthopedic department in government medical college, Jammu with distal femur fracture AO 33A, AO 33B and AO 33C during the period of June 2019 to February 2021 treated with open reduction and internal fixation with distal femur locking compression plate with 4.5 system. All patients were followed up for an average of 6 months. Outcome was assessed by Neer’s score. Results: The 42 patients (18 female and 24 males), mean age was 45 years (18 to 62 years) 26 cases were high energy trauma and out of 26, 8 patients had type I compound wound as per Gustilo Anderson classification and remaining 16 patients had trivial trauma. Out of 42 fractures treated, 38 fractures showed radiological signs of union within 6 months, remaining 3 cases showed delayed union which united completely by end of 10 months. One patient required bone grafting, 3 patients got infected, 2 implant failure, mean range of motion of all patients were 110 degrees. Conclusions: Open reduction and internal fixation of distal femur fractures with locking compression plate provides the good angular stability, prevents varus collapse and is gratefully helpful in osteoporotic patients.